Airspaces-derived exosomes contain disease-relevant protein signatures in a mouse model of cystic fibrosis (CF)-like mucoinflammatory lung disease - Mao, Yun; Suryawanshi, Amol; Patial, Sonika; Saini, Yogesh (Frontiers in Pharmacology, 2024)
Exosomes, membrane-bound extracellular vesicles, ranging from approximately 30–200 nm in diameter, are released by almost all cell types and play critical roles in intercellular communication. In response to the prevailing stress, the exosome-bound protein signatures vary in abundance and composition. To identify the bronchoalveolar lavage fluid (BALF) exosome-bound proteins associated with mucoinflammatory lung disease and to gain insights into their functional implications, we compared BALF exosomes-derived proteins from adult Scnn1b transgenic (Scnn1b-Tg+) and wild type (WT) mice. A total of 3,144 and 3,119 proteins were identified in BALF exosomes from Scnn1b-Tg+ and WT mice, respectively. Using cutoff criteria (Log2 fold-change > 1 and adjusted p-value < 0.05), the comparison of identified proteins revealed 127 and 30 proteins that were significantly upregulated and downregulated, respectively, in Scnn1b-Tg+ versus WT mice. In addition, 52 and 27 proteins were exclusively enriched in Scnn1b-Tg+ and WT mice, respectively. The identified exosome-bound proteins from the homeostatic airspaces of WT mice were mostly relevant to the normal physiological processes. The protein signatures enriched in the BALF exosomes of Scnn1b-Tg+ mice were relevant to macrophage activation and mucoinflammatory processes. Ingenuity pathway analyses revealed that the enriched proteins in Scnn1b-Tg+ mice contributed to the inflammatory responses and antimicrobial defense pathways. Selective proteins including, RETNLA/FIZZ1, LGALS3/Galectin-3, S100A8/MRP8, and CHIL3/YM1 were immunolocalized to specific cell types. The comparative analysis between enriched BALF exosome proteins and previously identified differentially upregulated genes in Scnn1b-Tg+ versus WT mice suggested that the compartment-/cell-specific upregulation in gene expression dictates the enrichment of their respective proteins in the lung airspaces. Taken together, this study demonstrates that the BALF exosome-bound protein signatures reflect disease-relevant disturbances. Our findings suggest that the exosomes carry disease-relevant protein signatures that can be used as a diagnostic as well as predictive biomarkers for mucoinflammatory lung disease.